Collapse dynamics of a vector vortex optical field with inhomogeneous states of polarization. (15th June 2015) - Chen, Rui-Pin; Zhong, Li-Xin; Chew, Khian-Hooi; Zhao, Ting-Yu; Zhang, Xiaobo
Abstract: Based on a pair of coupled 2D nonlinear Schrödinger equations, the collapse dynamics of a vector field with hybrid states of polarization (SoP) in a Kerr medium is demonstrated. The critical power for an optical field to collapse is present, and the full vectorial numerical simulations provide detailed information about the evolution and partial collapse of the vector field in a Kerr medium. Our results reveal that the optical field prefers to collapse in linearly-polarization, as a result of the self-focusing effect difference in linearly, elliptically and circularly polarized components. The SoP in the field cross-section changes and propagates with a spiral trajectory when the vector beams are imposed with a vortex. The vectorial effect on the collapse of a vector optical field can prevail over the noise even though it reaches 10% amplitude of the optical field. The unique feature of these structured collapses of a vector optical field may lead to new phenomena in the interaction of light with matter.